2021
DOI: 10.3390/medicina57101122
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Evolution to Pneumopericardium in Patient with COVID-19 Pneumonia Treated with High Flow Nasal Cannula

Abstract: Infection with severe acute respiratory syndrome coronavirus 2 causes coronavirus disease 2019 (COVID-19) which was revealed an official pandemic by the World Health Organization on 11 March 2020. The current pandemic, the third of this decade, is the worst in terms of suffering and deaths related. COVID-19 represents an unprecedented challenge for medical communities and patients around the world. High-resolution computed tomography of the chest (HRCT) is a fundamental tool in both management and diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Patients with asymptomatic PP can be managed conservatively, while those with tension PP should be managed with a pericardial aspiration to avoid possible hemodynamic deterioration. A drainage tube placement into the pericardial sac may be necessary if the PP is persistent or recurring [19]. Ghods et al reported a case of tension PP that required emergency echocardiography-guided catheter placement [11].…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…Patients with asymptomatic PP can be managed conservatively, while those with tension PP should be managed with a pericardial aspiration to avoid possible hemodynamic deterioration. A drainage tube placement into the pericardial sac may be necessary if the PP is persistent or recurring [19]. Ghods et al reported a case of tension PP that required emergency echocardiography-guided catheter placement [11].…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…The identification of several clinical conditions that represent risks of mortality for patients affected by COVID-19 [ 6 , 7 ], including the identification of several laboratory markers [ 8 , 9 ] that may play similar roles, attracted the attention of all workers in emergency departments. Furthermore, rare complications of treatments for COVID-19, such as spontaneous or ventilation-induced pneumothorax, pneumopericardium, or pneumopericardium, acquired great relevance during the outbreak [ 10 , 11 ]. Moreover, emergency departments adapted their activities to identify and manage the severe complications of vaccinations against SARS-CoV-2, such as vaccine-induced thrombocytopenia with thrombosis [ 12 ].…”
mentioning
confidence: 99%